PENGARUH MOTIVASI, KOMUNIKASI DAN BEBAN KERJA TERHADAP KINERJA KAYAWAN PADA TOKO CENTRAL GROSIR BULELENG - Eny Kasrianti, Komang; Sri Kasih, Ni Luh (Jurnal Daya Saing, 2024)
This study aims to determine the effect of motivation, communication, and workload on employee performance at the Central Wholesale Buleleng store. The method used in this research is quantitative using data obtained from questionnaires. The sample in this study were 30 people or all employees of the Central Wholesale Buleleng Store. Data analysis techniques using multiple linear regression. The results of this study indicate that: 1) The results of the above research state that Motivation cannot have a positive and significant effect on Employee Performance at the Central Wholesale Buleleng Store, this can be seen in the Partial Significant Test (t test) which obtained the tcount value of the Motivation variable (X1) is 1.148 and the ttable value is 1.706 then tcount < ttable (1.148 < 1.706) and also the significance test results obtained a significance value of 0.262> 0.05, then Ho is accepted and Ha is rejected. 2) The results of the above research state that Communication has a positive and significant effect on Employee Performance at the Central Wholesale Buleleng Store, this can be seen in the Partial Significant Test (t test) which obtained the tcount value of the Communication variable (X2) is 1.762 and the ttable value is 1.706 then tcount> ttable (1.762> 1.706) and also the significance test results obtained a significance value of 0.010 <0.05, then Ho is rejected and Ha is accepted. 3) The results of the above research state that Workload has a positive and significant effect on Employee Performance at the Central Wholesale Buleleng Store, this can be seen in the Partial Significant Test (t test) which obtained the tcount value of the Workload variable (X3) is 1.744 and the ttable value is 1.706 then tcount> ttable (1.744> 1.706) and also the significance test results obtained a significance value of 0.030 <0.05, then Ho is rejected and Ha is accepted.